Synthesis, characterization of Mo and Mn doped ZnO and their photocatalytic activity for the decolorization of two different chromophoric dyes - Umar, Khalid (Elsevier B.V., 2015)
Using sol-gel method, nano crystalline ZnO particles doped with different concentrations of molybdenum (Mo) and manganese (Mn) (0.2-1.0%) were synthesized. The structural and optical properties were studied with standard analytical techniques such as scanning electron microscopy (SEM), X-ray diffraction (XRD) and UV-vis spectroscopy. The crystalline nature of undoped and doped ZnO is indicated by XRD analysis. The SEM images of undoped ZnO showed irregular shape while doped ZnO showed fused supramolecular structure with rough surfaces. The photocatalytic activity of the synthesized particles (ZnO doped with Mo and Mn) was tested by studying the decolorization of two different chromophoric dyes namely Direct Yellow 27 (azo dye) and Acid Blue 129 (anthraquinone dye) with a 500 W halogen linear lamp in the presence of atmospheric oxygen as a function of irradiation time. The results indicate that ZnO with dopant concentration of 0.60% Mo and 0.80% Mn showed the highest photocatalytic activity as compared to the other dopant concentrations for the decolorization of both dyes. In the case of azo dye, 84% decolorization was found while in case of anthraquinone dye, 66% decolorization took place using 0.60% Mo in 390 min.